CULTIVO DE BABY LEAF DE CHICÓRIA: SISTEMAS DE PROTEÇÃO E ESPAÇAMENTOS DE PLANTIO - Espíndola, Jhone de Souza (2012)
The vegetables like baby leaf are characterized by the early harvest of cultivated species, and the production and marketing of these are still incipient in Brazil. To assist the production techniques, experiment was conducted between August and October 2011 with the objective of evaluating the productive responses of baby leaf chicory cv. Escarole Lisa in different environmental conditions and spacing between plants. The experimental design was a randomized complete block with 04 replications with treatments arranged in split-split. The primary factor was the growing environment (TP- low plastic tunnel; AG-white non woven; AN-natural environment), the secondary factor was spacing between plants (E1- 2 x 5 cm; E2- 4 x 5 cm; E3- 2 x 10 cm; E4- 5 x 10 cm) and tertiary factor was evaluation periods (14, 21, 28, 35 and 42 days after sowing - DAS). The characteristics evaluated were plant height (AP), leaf area index (IAF), number of leaves per plant (NF), length (CMF) and width (LMF) of the largest leaf, fresh fitomassas (FMF) and dry (FMS) and plant productivity (P). In protect cultivation, the plants reached the harvesting stage (plant height = 10 cm) at 35 days after harvest while (DAS), in the natural environment was at 41 DAS. The NF, at the point of harvest, was higher for plants grown in AN, differentiating the results for AP, CMF, LMF, FMF and IAF. FMF values in TP and AG were higher until it reaches the point of harvest. For growing baby leaf chicory, it was found that the average temperature between 18 and 19ºC was the most suitable for plant growth under protected cultivation in relation to the natural environment. The interaction between different environmental conditions and spacing between plants was significant only for FMF. For cultivation under AG, the spacing between plants E2 and E4 resulted in plants with FMF higher than the spacing between plants E1 and E3. In relation to FMF, Plants grown in AN had lower values than those under TP and AG, except for E3, where plants under GA did not differ from those of AN. For the interaction between evaluation periods and spacing between plants, there was a significant effect for FMF, FMS and IAF. It was found that the FMF and FMS in E1 and E3 were lower than E2, and E4 in 35 DAS. The results of IAF demonstrated that plants grown in smaller spacing between plants (E1) had greater leaf area expansion compared to those in lower density (E4). At harvesting stage, there was a higher productivity when the combination was used spacing between plants E1 and cultivation environment AN. It was verified that is possible to obtain precocity in the cultivation of baby leaf chicory without loss of quality in TP and AG. When all the plants reach the harvesting stage, it is possible to obtain higher productivity using the natural environment (AN) together with the spacing between plants (E1). The use of protect cultivation (non-woven and low tunnel) and spacing E1 are suitable for the cultivation and marketing of whole plant (unit sales) of baby leaf chicory instead of selling by weight.